MAKNA KEPATUTAN DAN KEWAJARAN BERKAITAN DENGAN TANGGUNG JAWAB SOSIAL PERUSAHAAN DALAM UNDANG – UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - Rachmad Robby Nugraha; Siti Hamidah; Moch. Fadli (Universitas Negeri Malang, 2018)
the purpose of the author of this article is to discuss the meaning of propriety and reason- ableness in Article 74 paragraph (2) of Law Number 40 of 2007 concerning Limited Liability Compa- nies (UUPT) on a corporate social responsibility agreement in the distribution. The method uses normative legal studies with legislative approaches, concepts, and case studies. The propriety meaning is conformity based on balance, meaning that it must fulfill the element of conformity with the situation or the balance between the company’s ability to risk the activities of the company. Fairness is interpreted as something that should or should be done based on the order and the appropriate rules. Compliance and reasonableness are viewed from the point of view of the amount that is spent on the company’s CSR must be in proportion and not contrary to the provisions of the legislation. Compliance and reasonableness are related to the number, objectives, and form of the agreement.